Pengaruh Penggunaan Metode Mind Mapping Terhadap Hasil Belajar Siswa Kelas IV MI Al-Abror Pandansili Mojokerto - Rif'an Fauzi; Syahnaja Syahnaja (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research is motivated by the low student learning outcomes because most teachers teach by using learning methods that are less efficient. So the researchers conducted learning research using the mind mapping method. The results of this study indicate that based on the calculation of the ANOVA test, for learning outcomes obtained the value of Sig. of  0.009. Value of Sig. < 0.05 then is accepted. So it can be concluded that there is an effect of the mind mapping method on the learning outcomes of fourth-grade students on Economic Activities. from the test of student learning outcomes in the experimental class and the control class in social studies subjects on the application of the mind mapping method at MI Al-Abror Pandansili Mojokerto in the form of 25 multiple choice questions that have been tested for validity.